Penerapan Metode Analytical Hierarchy Process dalam Penentuan Supplier Terbaik PT Supraco Indonesia - Naim Munah, Khasanah; Farahdiansari, Ardana Putri (Universitas Bojonegoro, 2023)
Inventory management at PT Supraco Indonesia ensures accurate and timely material inventory, proper delivery, and quality control according to predefined standards. The supplier selection process is analyzed using the AHP (Analytical Hierarchy Process) method, a decision support model that breaks down complex multi-criteria problems into a hierarchical structure. AHP considers validity and consistency tolerance limits in choosing criteria and alternatives. The key criterion influencing supplier selection is Quality, with a weight of 0.73. Among alternatives, Aqua Terra scored highest for Quality, Manunggal for Cost, and Sentra Medika for Delivery. Based on the overall analysis, Aqua Terra emerged as the best supplier, while Sentra Medika had the lowest performance.